Comparative evaluation of ondansetron, palonosetron, and dexamethasone for antiemetic prophylaxis in cesarean section under spinal anaesthesia - Vankudoth Bhaskar; Jitendra Agrawal; Ankita Gupta; Ashish Mohan M (Asian Journal of Medical Sciences)
Background: Spinal anesthesia is the most common regional anesthesia used to provide surgical anesthesia for cesarean section. Nausea and vomiting are common symptoms experienced by patients undergoing cesarean section.